Morphologic Analysis of Compound Words - Wingert, F. (Methods of Information in Medicine, 1985)
Algorithms for morphologic analysis of compound words and related dictionary structures are described’ on the basis of different word models. The algorithms are formulated in Backus-Naur form as well as Augmented Transition Networks. The results of applying the algorithms to the 56,509 different words of the “Systematisierte Nomenklatur der Medizin” (SNOMED) are presented.
Keywords: Computational Linguistics; Morphologic Analysis; Word Model; SNOMED